The Political Economy of Productivity. The Case of Chile - Cristobal Aninat; Jose Miguel Benavente; Ignacio Briones; Nicolas Eyzaguirre; Patricio Navia; Jocelyn Olivari (Inter-American Development Bank (IDB), 2010)
This paper analyzes the political economy of productivity-related policymaking in Chile following a political transaction cost model (Spiller and Tommasi, 2003; Murillo et al., 2008). The main findings indicate that i) the Chilean policymaking process (PMP) was successful in the 1990s in implementing productivityenhancing policies, but as the country moved to a higher stage of development, the PMP grew less adept at generating the more complex set of policies needed to increase productivity at this stage; and ii) the Chilean PMP is less transparent than previously thought (Aninat et al., 2008), thus allowing political actors to favor private interests without being punished by the electorate. This has become apparent as the more sophisticated reforms needed at this stage of development require a deeper and more consolidated democracy.
Keywords: L52; O25; O40; 330; Economic policy; Institutional reforms; Productivity; Pensions; Education; Innovation; State modernization; Competitiveness; Chile